The reef-building coral Galaxea fascicularis: a new model system for coral symbiosis research - Puntin, Giulia; Craggs, Jamie; Hayden, Róisín; Engelhardt, Kara E.; McIlroy, Shelby; Sweet, Michael; Baker, David M.; Ziegler, Maren; Justus Liebig University Giessen (My University, 2023)
Reef-building corals owe their evolutionary success to their symbiosis with unicellular algae (Symbiodiniaceae). However, increasingly frequent heat waves lead to coral mass-bleaching events and pose a serious threat to the survival of reef ecosystems. Despite significant efforts, a mechanistic understanding of coral–algal symbiosis functioning, what leads to its breakdown and what can prevent it, remains incomplete. The main obstacles are low amenability of corals to experimental handling and, owing to its obligatory nature, the difficulties of manipulating the coral–algal association. Indeed, many studies on the symbiotic partnership are conducted on other cnidarian model organisms and their results may therefore not be fully transferable to tropical reef-building corals. Here, we identify the tropical stony coral species Galaxea fascicularis as a novel candidate coral model system. Individual polyps of this species can be separated, enabling highly replicated genotype studies, and are well suited to experimental investigation of the symbiosis as they can be easily and effectively rid of their algal symbionts (bleached). We show that bleached adult individuals can reestablish symbiosis with non-native symbionts, and we report the completion of the gametogenic cycle ex situ, with the successful spawning in aquaria over multiple years. These achievements help overcome several of the major limitations to direct research on corals and highlight the potential of G. fascicularis as an important new model system for investigations of symbiosis functioning and manipulation.
Keywords: ddc:570